2024
DOI: 10.1017/ash.2024.42
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of the COVID-19 vaccines in the prevention of post-COVID conditions in children and adolescents: a systematic literature review and meta-analysis

Maria Celidonio Gutfreund,
Takaaki Kobayashi,
Gustavo Yano Callado
et al.

Abstract: Objective: We performed a systematic literature review and meta-analysis on the effectiveness of coronavirus disease 2019 (COVID-19) vaccination against post-COVID conditions (long COVID) in the pediatric population. Design: Systematic literature review/meta-analysis. Methods: We searched PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL), EMBASE, Cochrane Central Register of Controlled Trials, Scopus, and Web of Science from December 1, 2019, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The effectiveness of full vaccination against SARS-CoV-2 infection was estimated to be from 70.4% by the ChAdOx1 nCoV-19 vaccine (AZD1222; Oxford-AstraZeneca) to 95% by the BNT162b2 mRNA COVID-19 vaccine (Pfizer-BioNTech). When the prevention of hospitalization and Vaccines 2024, 12, 553 2 of 17 intensive care unit admission and severe disease were assessed, the effectiveness of vaccination ranged between 89 and 93% [3][4][5]. The WHO suggested that a clear demonstration of efficacy should be a minimum criterion for any acceptable COVID-19 vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of full vaccination against SARS-CoV-2 infection was estimated to be from 70.4% by the ChAdOx1 nCoV-19 vaccine (AZD1222; Oxford-AstraZeneca) to 95% by the BNT162b2 mRNA COVID-19 vaccine (Pfizer-BioNTech). When the prevention of hospitalization and Vaccines 2024, 12, 553 2 of 17 intensive care unit admission and severe disease were assessed, the effectiveness of vaccination ranged between 89 and 93% [3][4][5]. The WHO suggested that a clear demonstration of efficacy should be a minimum criterion for any acceptable COVID-19 vaccine.…”
Section: Introductionmentioning
confidence: 99%